(untitled) (Journal of Mathematics Mechanics and Computer Science, 2021)
Abstract. The stress state of an element of a thick-walled pipeline when ovalizing a cross section is studied under conditions of power and corrosion effect in the statement of plane deformation. The material of the element under the influence of external loads goes into an elastic-plastic state. The corrosive effect of a pumped medium leads to softening of the material in the plastic zone. This softening of the material is taken into account by a special inhomogeneity function in the Tresca-Saint-Venant plasticity condition. The elastic-plastic problem for an thick-walled elliptical element under uniform external and internal pressure is considered in non-axisymmetric setting. The problem is solved by the method of sharing static and physical equations for the considered elastoplastic material and the perturbation method in the theory of an elastoplastic body. An assessment of the strength and bearing capacity of a loaded thick-walled elliptical element under presence and absence of corrosion damage is given.